Perceived Clinical Practice Competency and Associated Factors Among Undergraduate Students of Medicine and Health Science Collage in Dilla University, SNNPR, Ethiopia - Tesfaye TS; Alemu W; Mekonen T (Advances in Medical Education and Practice, 2020)
Tinsae Shemelise Tesfaye,1 Wagaye Alemu,1 Tadesse Mekonen2 1Public Health Department, College of Medicine and Health Science, Dilla University, Dilla, Ethiopia; 2Food Science and Nutrition Directorate, Ethiopian Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Tinsae Shemelise TesfayePublic Health Department, College of Medicine and Health Science, Dilla University, Dilla, EthiopiaTel +251910644517Email justtinsae@gmail.comBackground: The dynamic and uncertain nature of the healthcare environment requires competent health professionals to manage the changing environment. However, globally and regionally there is a shortage of competent health professionals. Understanding the causes of poor performance of healthcare is crucial to provide high-quality healthcare service. So this study aims to assess perceived clinical competence and associated factors among undergraduate medicine and health science students at Dilla University, medical and health Science College.Methods: Institutional-based cross-sectional study was conducted among 267 students. Initially, departments were stratified, then simple random sample was used to select students. A 2 days of training was given for data collectors and supervisors. Data were entered into Epi-info version 7 and analyzed using Stata version 12. Logistic regression analysis was used to assess associated factors of clinical competency.Results: A total of 267 students participated in this study. The majority of students were males 197 (73.8%) and more than half of the participants 186 (69.7%) were in the age group of 20 to 24 years. The study found only 39.3%, 95% CI (33.3, 44.9) of the participants perceived themselves as clinically competent. This study also identified instructor provided constructive feedback (AOR= 2.12, 95% CI =1.164– 3.861), instructor orientation about assessment method (AOR=1.855 95% CI =1.03– 3.408) and staff encouragement during clinical practice (AOR= 2.608, 95% CI= 1.425– 4.77) were statistically significant factors.Conclusion and Recommendation: In this study, perceived clinical competency was 39%. Teachers should give constructive feedback to their students to boost their confidence and ability. Furthermore, nationally there should be standard and clear assessment methods in which teachers, school administrators and responsible stakeholders should briefly explain assessment methods to their students and it also needs an action to improve the interaction between staff and students.Keywords: clinical practice, competency, undergraduate health students, Dilla University